2010
DOI: 10.3184/030823410x12677394014276
|View full text |Cite
|
Sign up to set email alerts
|

Novel Entry into 5-Decarboxydibenzofurans via Smiles Rearrangement of the Lichen Para-Depside, Erythrin

Abstract: Erythrin, isolated in 7.3% yield from the lichen Roccella montagnei, was converted via a Smiles rearrangement to a series of diphenyl ethers. Those with a free carboxylic acid at C-1 underwent a novel decarboxylative oxidative cyclisation in the presence of Pd(OAc) 2 to produce 5-decarboxydibenzofurans. All compounds were assayed for their antioxidant and β-glucuronidase enzyme inhibitory activity.Lichens are symbiotic organisms of fungi (mycobionts) and algae (phycobionts) comprising about 18,000 species whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…A detailed chromatographic fractionation of its methanol extract led to the isolation of five new compounds (15) alongside seven metabolites (612) already described ( Fig. 1 D-(+)-Montagnetol (6), D-(+)-erythrin (8) and lecanoric acid (9) are the main markers of R. montagnei (Huneck and Folhman, 1967;Basset et al, 2010;Thadhani et al, 2010) and were isolated as major compounds of this lichen. Besides orsellinic acid (11) and methyl orsellinate (12) (Lopes et al, 2008) which correspond to monoaromatic moieties found in many lichens, five new montagnetol derivatives (15) were isolated from R. montagnei.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…A detailed chromatographic fractionation of its methanol extract led to the isolation of five new compounds (15) alongside seven metabolites (612) already described ( Fig. 1 D-(+)-Montagnetol (6), D-(+)-erythrin (8) and lecanoric acid (9) are the main markers of R. montagnei (Huneck and Folhman, 1967;Basset et al, 2010;Thadhani et al, 2010) and were isolated as major compounds of this lichen. Besides orsellinic acid (11) and methyl orsellinate (12) (Lopes et al, 2008) which correspond to monoaromatic moieties found in many lichens, five new montagnetol derivatives (15) were isolated from R. montagnei.…”
Section: Resultsmentioning
confidence: 90%
“…montagnei (Feige et al, 1986;Huneck and Follmann, 1967;Thadhani et al, 2010;Parrot et al, 2015). The genus Roccella has been recently revised, describing 24 main species which are restricted to coastal habitats (Tehler et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The eleven known compounds ( 7 – 17 ) were identified as 4-methoxycarbonyl diorcinol ( 7 ) [ 10 ], diorcinol ( 8 ) [ 11 ], glyceryl diorcinolic acid ( 9 ) [ 12 ], cordyol C ( 10 ) [ 14 ], aspergilol E ( 11 ) [ 13 ], 4-hydroxy-2-(3′-hydroxy-4-methoxycarbonyl-5′-methylphenoxy)-6-methylbenzoic acid ( 12 ) [ 16 ], gibellulin B ( 13 ) [ 11 ], diorcinols F ( 14 ) [ 30 ], 3,7-dihydroxy-1,9-dimethyldibenzofuran ( 15 ) [ 31 ], 4-carboxydiorcinal ( 16 ) [ 32 ] and aspermutarubrol ( 17 ) [ 33 ] by comparison of their spectroscopic data to those reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…The genus Aspergillus , with over 200 species, has attracted considerable attention as a rich source of bioactive compounds including polyketides, peptides, terpenoids [ 7 , 8 , 9 ] and others. Diphenyl ethers are a group of polyketides with simple structures that are widely distributed in various species of Aspergillus [ 10 , 11 , 12 , 13 ] and have been reported to show significant diverse bioactivities, such as antiviral [ 14 ], antimicrobial [ 14 , 15 ], β -glucuronidase enzyme inhibitory [ 16 ], radical-scavenging [ 17 ], cytotoxicity [ 10 , 14 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], anti-Aβ 42 aggregation [ 24 ], regulating actin function [ 25 ] and phytocidal activities [ 26 ]. The cytotoxicity of diphenyl ethers against a variety of cancer cell lines has been widely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Sri Lankan plants have been tested for biological activity with promising results (Hewage et al, 1997). In addition, the structural diversity among Sri Lankan higher and lower plants are typified by the discovery of alkaloids, (Puvenendran et al, 2008), compounds with iron chelating function (Kathirgmanathar et al, 2006;Karunaratne et al, 2005;Tezuka et al, 1994;Bandara et al, 1990), phenolic acids, ketones (Thadhani et al, 2012;Thadhani et al, 2010), five-membered ring butenolides and hydrazulenones (Piers and Karunaratne, 1984;Carr et al, 2012) all of them have been shown to possess a variety of biological activities. However, there is a paucity of studies on the chemistry and biological activity of Sri Lankan noxious weeds.…”
Section: Introductionmentioning
confidence: 99%